2011
DOI: 10.1113/jphysiol.2011.220186
|View full text |Cite
|
Sign up to set email alerts
|

Protein‐energy malnutrition during early gestation in sheep blunts fetal renal vascular and nephron development and compromises adult renal function

Abstract: Non-technical summaryA poor diet during pregnancy has been linked to long-term health outcomes for the baby, such as an increased risk of diseases of the heart and kidney. We show in an experimental model that recreates a poor diet during pregnancy, i.e. a diet low in protein with adequate energy, that kidney development in the baby is affected in such a way as to reduce the potential for new blood vessels to form. This results in a greater number of important, functional kidney cells spontaneously dying. Late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 77 publications
3
29
0
Order By: Relevance
“…It has been demonstrated that intrauterine growth restriction can induces apoptosis in fetal kidney and in beta cells of pups compromising the adult renal function and insulin secretion, respectively [52], [53]. Nevertheless, the maternal protein restriction during lactation had a protective effect on the thymocytes with lower spontaneously apoptosis rate, without altering the proliferative response.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that intrauterine growth restriction can induces apoptosis in fetal kidney and in beta cells of pups compromising the adult renal function and insulin secretion, respectively [52], [53]. Nevertheless, the maternal protein restriction during lactation had a protective effect on the thymocytes with lower spontaneously apoptosis rate, without altering the proliferative response.…”
Section: Discussionmentioning
confidence: 99%
“…In rodent, despite strictly controlled conditions, the nephron endowment can vary by an average of 10% to 15% for a birth weight situated within normal range [122, 123]. Events that occur during the early stage of nephrogenesis can induce a nephron deficit without affecting birth weight [124127]. Exposure to maternal low protein diet and administration of a short course of glucocorticoids during the early stage of nephrogenesis, in rodents (E14–17) and in sheep (E80), are sufficient to reduce nephron endowment (−20% to −40%) without inducing low birth weight [124126].…”
Section: Birth Weight Nephron Endowment and Ckdmentioning
confidence: 99%
“…The underlying causes are still to be fully established, but evidence points to developmental changes in organ systems which result in their limited functional capacity at maturity. Kidney development has been shown to be adversely impacted by maternal undernutrition during gestation with the result that offspring possess fewer nephrons than controls [6][7][8][9][10][11]. A reduced nephron complement has been strongly associated with a predisposition towards hypertension, coronary heart disease and renal disease [12][13][14] and animal studies have provided experimental support for these observations [6,15,16].…”
Section: Introductionmentioning
confidence: 88%